Cre-loxP-mediated genetic lineage tracing: Unraveling cell fate and origin in the developing heart - Wang, Tao; Chen, Xinzhe; Wang, Kai; Ju, Jie; Yu, Xue; Wang, Shaocong; Liu, Cuiyun; Wang, Kun (Frontiers in Cardiovascular Medicine, 2023)
The Cre-loxP-mediated genetic lineage tracing system is essential for constructing the fate mapping of single-cell progeny or cell populations. Understanding the structural hierarchy of cardiac progenitor cells facilitates unraveling cell fate and origin issues in cardiac development. Several prospective Cre-loxP-based lineage-tracing systems have been used to analyze precisely the fate determination and developmental characteristics of endocardial cells (ECs), epicardial cells, and cardiomyocytes. Therefore, emerging lineage-tracing techniques advance the study of cardiovascular-related cellular plasticity. In this review, we illustrate the principles and methods of the emerging Cre-loxP-based genetic lineage tracing technology for trajectory monitoring of distinct cell lineages in the heart. The comprehensive demonstration of the differentiation process of single-cell progeny using genetic lineage tracing technology has made outstanding contributions to cardiac development and homeostasis, providing new therapeutic strategies for tissue regeneration in congenital and cardiovascular diseases (CVDs).